Experimental study of laminated glass window responses under impulsive and blast loading - Zhang, Xihong; Hao, Hong; Wang, Z. (Elsevier Ltd, 2015)
Laminated glass panes are widely adopted as blast-resistant glass windows to mitigate the hazard from ejecting fractured glass fragments. The response of laminated glass windows under blast loads is often predicted by equivalent static analysis or simplified equivalent single degree of freedom (SDOF) analysis. The equivalent SDOF and equivalent static analyses are also respectively adopted in UFC and ASTM design guide for glass window designs. Owing to the inherent problems, the SDOF analysis can only predict the global responses of glass windows and the predictions are not necessarily always satisfactory. Therefore the accuracy and applicability of the SDOF analysis is sometimes questioned. Often numerical simulations and/or experimental tests have to be carried out for reliable predictions of laminated glass window responses to blast loads. In this study, experimental tests on laminated glass windows subjected to impact and blast loads were carried out to evaluate the accuracy of available analyses and design methods. Pendulum impact tests were conducted first on laminated panes of various thicknesses. Full-scale field blast tests were performed on laminated glass windows of dimension 1.5 m × 1.2 m. Glass pane deflections were monitored by mechanical linear voltage displacement transducer (LVDT) and high-speed cameras. The responses of the tested windows are compared with the estimations of SDOF models and design standards in this paper. Available blast testing data by other researchers are also included together with the current testing data to evaluate the accuracy of the SDOF and equivalent static analyses defined in the design guides. The adequacy of these simplified approaches in predicting laminated glass window responses to blast loads is discussed.